2018
DOI: 10.4254/wjh.v10.i11.877
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac stress testing and coronary artery disease in liver transplantation candidates: Meta-analysis

Abstract: AIMTo evaluate the diagnostic value of dobutamine stress echocardiography (DSE) and myocardial perfusion scintigraphy (MPS) in predicting coronary artery disease (CAD) in cirrhotic patients listed for liver transplantation (LT), using invasive coronary angiography (ICA) as gold-standard.METHODSRetrieval of studies was based on Medical Subject Headings and Health Sciences Descriptors, which were combined using Boolean operators. Searches were run on the electronic databases Scopus, Web of Science, EMBASE, MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It revealed that the pooled sensitivity was 28% and 61% and specificity was 82% and 74% for DSE and MPS, respectively. It is notable that the risk factors that prompted coronary catheterization in most of the studies analyzed in this meta-analysis were not identified which can certainly impact the observed sensitivity [14]. It has been proposed that liver transplant candidates with multiple conventional CAD risk factors need to undergo coronary catheterization.…”
Section: Coronary Artery Disease Post Liver Transplantationmentioning
confidence: 96%
“…It revealed that the pooled sensitivity was 28% and 61% and specificity was 82% and 74% for DSE and MPS, respectively. It is notable that the risk factors that prompted coronary catheterization in most of the studies analyzed in this meta-analysis were not identified which can certainly impact the observed sensitivity [14]. It has been proposed that liver transplant candidates with multiple conventional CAD risk factors need to undergo coronary catheterization.…”
Section: Coronary Artery Disease Post Liver Transplantationmentioning
confidence: 96%
“…In a study of patients with NAFLD undergoing LT evaluation, 37% did not reach target heart rate during stress echocardiography[ 89 ]. Tests of cardiac function in NAFLD patients may not reveal the severity of disease: A meta-analysis of cardiac stress test results during LT evaluation revealed a pooled sensitivity of 21-28% and specificity of 82-91% for coronary artery disease[ 90 ]. Dobutamine stress echocardiography has poor predictive value for post-operative cardiovascular events, with a reported positive predictive value of 6.7% and negative predictive value of 83.5%[ 91 ].…”
Section: Pre-transplant Considerations For Patients With Nashmentioning
confidence: 99%
“…According to a meta-analysis which evaluated the diagnostic accuracy of dobutamine SE in diagnosing hemodynamically significant coronary artery stenoses, there is a high heterogeneity among studies, demonstrating low sensitivity of 28% and high specificity of 82% [73]. However, in most of those studies only a small proportion of the patients underwent coronary angiography.…”
Section: Stress Echocardiography In Lt Candidates Current Knowledgementioning
confidence: 99%
“…During vasodilator studies, ischemia is induced by coronary steal of blood flow away from the stenotic artery [81] and thus, oxygen delivery is not determined by heart rate and cardiac work increase [82]. For this reason myocardial perfusion studies using scintigraphy have shown higher sensitivity of 62% in diagnosing hemodynamically significant CAD, but with lower specificity [73]. However, with perfusion studies, autonomic dysfunction and blunted adrenergic response cannot be evaluated even though they are the hallmark of cirrhotic cardiomyopathy.…”
Section: Stress Echocardiography In Lt Candidates Future Perspectivesmentioning
confidence: 99%